Preparation method of modified silicon dioxide material for lead-acid battery

By using modified silica materials in lead-acid batteries, the toughness of the material is improved through high temperature reaction and copolymerization reaction, the problem of high brittleness of silica materials in existing lead-acid batteries is solved, and the processing difficulty and cost are reduced, and the processing is improved. Productivity.

CN119160900APending Publication Date: 2024-12-20江苏永达电源股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411227581.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The silica material in existing lead-acid batteries is highly brittle, easy to break, difficult to process, high cost and low production efficiency.

Method used

By adding carbonate, silicone, coupling agent and plasticizer to quartz sand, high-temperature reaction and copolymerization reaction are carried out to form modified silica material, improving its impact toughness and flexibility and reducing brittleness.

Benefits of technology

It effectively reduces the damage of silica under impact or pressure, reduces processing difficulty and cost, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160900A_ABST
    Figure CN119160900A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a preparation method of a modified silicon dioxide material for a lead-acid battery, and the preparation method comprises the following steps: S1, preparing the following materials in parts: 100-900 parts of quartz sand, 10-800 parts of carbonate, 1-520 parts of organic silicon, 1-300 parts of a coupling agent, 1-210 parts of a plasticizer and 100-800 parts of smelting waste slag; s2, the smelting waste residues are treated, impurities are filtered out, and components for preparing silicon dioxide are extracted for standby application; and S3, grinding and washing quartz sand, mixing the standby components in the step S2 with the coupling agent and the plasticizer, and putting the mixture into carbonate. The brittleness of the silicon dioxide is reduced by adding the additive for increasing the brittleness into the quartz sand, and after the silicon dioxide is preliminarily prepared, the modified silicon dioxide material is formed by blending and copolymerizing the silicon dioxide and the organic silicon, so that the damage condition is reduced after the silicon dioxide is impacted or pressed, the processing difficulty is reduced, and the processing cost is reduced; and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and specifically relates to a method for preparing a modified silicon dioxide material for a lead-acid battery. Background Art

[0002] Lead-acid battery is a storage battery whose electrodes are mainly made of lead and its oxides, and whose electrolyte is sulfuric acid solution. In the discharge state of lead-acid battery, the main component of the positive electrode is lead dioxide, and the main component of the negative electrode is lead; in the charging state, the main components of the positive and negative electrodes are both lead sulfate. The nominal voltage of a single-cell lead-acid battery is 2.0V, which can be discharged to 1.5V and charged to 2.4V. In application, 6 single-cell lead-acid batteries are often connected in series to form a lead-acid battery with a nominal voltage of 12V. In PE separators, silicon dioxide is both the skeleton of the PE separator and the pore-forming agent of the PE separator, accounting for about 60% of the total weight of the separator. The pore size of the PE separator affects the degree of short circuit of the lead dendrites. The porous structure of the separator allows the electrolyte to diffuse freely and the ions to migrate. Silica materials are usually brittle and are prone to breakage after being impacted or pressed. In addition, the processing is difficult, the processing cost is high, and the production efficiency is low. In this regard, we propose a preparation method of modified silicon dioxide materials for lead-acid batteries. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing a modified silicon dioxide material for a lead-acid battery to solve the above technical problems.

[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a modified silicon dioxide material for a lead-acid battery, the preparation steps being:

[0005] S1. Prepare the following materials: 100-900 parts of quartz sand, 10-800 parts of carbonate, 1-520 parts of organosilicon, 1-300 parts of coupling agent, 1-210 parts of plasticizer and 100-800 parts of smelting waste slag;

[0006] S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside;

[0007] S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide;

[0008] S4, filtering and washing the preliminary silica to obtain a silica product;

[0009] S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material;

[0010] S6. Conduct quality inspection on the modified silica material.

[0011] Preferably, the specific proportions of materials in step S1 are: 800 parts of quartz sand, 600 parts of carbonate, 220 parts of silicone, 200 parts of coupling agent, 110 parts of plasticizer and 650 parts of smelting waste slag.

[0012] Preferably, the quartz sand is one of river sand, sea sand, mountain sand and crystalline quartz sand, the carbonate is one of normal salt, acid salt and basic carbonate, the organosilicon is one of organosilicon monomer and organosilicon intermediate, the coupling agent is one of silane coupling agent, titanate coupling agent, aluminate coupling agent, bimetallic coupling agent, phosphate coupling agent and borate coupling agent, the plasticizer is one of aliphatic dibasic acid ester, phthalate and benzoate, and the smelting waste slag includes the residue of ironmaking waste slag, steelmaking waste slag, ferroalloy smelting waste slag and light metal smelting waste slag;

[0013] Coupling agent is a chemical substance that can connect inorganic and organic substances. By modifying nano-silicon dioxide with coupling agent, its impact toughness and tensile properties can be significantly improved, thereby improving its brittleness.

[0014] The brittleness of silica can also be improved by adding plasticizers to the material, which can increase the flexibility and ductility of the material, thereby reducing the possibility of brittle fracture.

[0015] Preferably, in step S2, the step of filtering out impurities from the smelting waste slag is performed by placing the smelting waste slag into a crusher in advance for crushing treatment to reduce the particle size, utilizing the density difference of different metals to perform a preliminary screening of the metal and non-metallic substances in the waste slag through gravity screening equipment, and then utilizing the conductivity difference of different metals to perform a secondary screening through an electric separation equipment to screen out the conductive metal and the non-conductive metal, and finally dissolving the metal ions in the waste slag through an acid leaching method, and extracting the prepared silicon dioxide component through precipitation crystallization.

[0016] Preferably, in step S3, the quartz sand grinding step is performed by using a hammer crusher to crush the quartz sand, breaking the large particles of quartz sand into small particles, and then grinding the small particles of quartz sand using a dry method; the quartz sand washing step is performed by soaking the ground small particles of quartz sand in clean water for 5 hours. After the soaking time is completed, the small particles of quartz sand are taken out, sieved and filtered, and placed in the sun for drying, and the quartz sand is washed after the water is dried.

[0017] Preferably, in step S3, the coupling agent and the plasticizer are mixed simultaneously and added to the carbonate; the high temperature reaction temperature is 900° C. and the reaction time is 5 hours.

[0018] Preferably, in step S4, a glass fiber filter is used for silica filtration, a transparent supernatant is first passed through the filter, the suspended matter is precipitated, the supernatant is discarded, and the precipitate is filtered out with a filter, a suction filtration operation is performed, and finally a drying operation is performed to obtain filtered silica; silica washing is performed by washing the filtered silica in clean water to remove residual chemical solvents and impurities.

[0019] Preferably, in step S5, the silica product is co-polymerized with the organosilicon by chemical bonding to form a modified composite material, an initiator is added to the mixed silica to initiate the polymerization reaction, and the reaction conditions are controlled to form a new polymer network structure during the polymerization process.

[0020] Preferably, the quality test of the modified silicon dioxide material in step S6 includes testing the brittleness and strength of the silicon dioxide.

[0021] Preferably, the silicon dioxide brittleness detection steps are:

[0022] A1. Sample preparation: preparing a silica sample;

[0023] A2. Prepare testing equipment and select universal material testing machine and impact testing machine as testing equipment;

[0024] A3. Set the test parameters of the equipment, including loading speed, loading method and test temperature;

[0025] A4. Install the sample in the fixture of the test equipment to ensure that the sample is firmly fixed and evenly stressed;

[0026] A5. Start the test equipment, test the samples according to the set parameters, and observe and record the deformation and crack extension of the samples during loading;

[0027] A6. When the sample breaks, stop the test and record the relevant data, including the maximum load and breaking strength.

[0028] A7. Analyze the data and calculate the brittleness index of the sample;

[0029] The calculation formula is:

[0030] Where Ki is the output value, P is the maximum force that the sample can withstand, S is the distance between the sample and the support point, B is the sample thickness, and W is the width of the sample.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present application reduces the brittleness of silicon dioxide by adding an additive that increases brittleness into quartz sand, and after the silicon dioxide is initially prepared, forms a modified silicon dioxide material by blending and copolymerizing with organic silicon, which reduces the possibility of breakage after being impacted or pressurized, reduces the difficulty and cost of processing, and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The figure is a flowchart of the steps for preparing silicon dioxide according to the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A method for preparing a modified silicon dioxide material for a lead-acid battery, the preparation steps being:

[0037] S1. Prepare the following materials: 800 parts of quartz sand, 600 parts of carbonate, 220 parts of silicone, 200 parts of coupling agent, 110 parts of plasticizer and 650 parts of smelting waste slag;

[0038] S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside;

[0039] S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide;

[0040] S4, filtering and washing the preliminary silica to obtain a silica product;

[0041] S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material;

[0042] S6. Conduct quality inspection on the modified silica material.

[0043] Example 2

[0044] A method for preparing a modified silicon dioxide material for a lead-acid battery, the preparation steps being:

[0045] S1. Prepare the following materials: 700 parts of quartz sand, 550 parts of carbonate, 250 parts of silicone, 110 parts of coupling agent, 110 parts of plasticizer and 750 parts of smelting waste slag;

[0046] S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside;

[0047] S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide;

[0048] S4, filtering and washing the preliminary silica to obtain a silica product;

[0049] S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material;

[0050] S6. Conduct quality inspection on the modified silica material.

[0051] Example 3

[0052] A method for preparing a modified silicon dioxide material for a lead-acid battery, the preparation steps being:

[0053] S1. Prepare the following materials: 600 parts of quartz sand, 750 parts of carbonate, 210 parts of silicone, 200 parts of coupling agent, 90 parts of plasticizer and 720 parts of smelting waste slag;

[0054] S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside;

[0055] S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide;

[0056] S4, filtering and washing the preliminary silica to obtain a silica product;

[0057] S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material;

[0058] S6. Conduct quality inspection on the modified silica material.

[0059] Example 4

[0060] A method for preparing a modified silicon dioxide material for a lead-acid battery, the preparation steps being:

[0061] S1. Prepare the following materials: 210 parts of quartz sand, 125 parts of carbonate, 120 parts of silicone, 220 parts of coupling agent, 200 parts of plasticizer and 800 parts of smelting waste slag;

[0062] S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside;

[0063] S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide;

[0064] S4, filtering and washing the preliminary silica to obtain a silica product;

[0065] S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material;

[0066] S6. Conduct quality inspection on the modified silica material.

[0067] Comparative Example 1

[0068] The preparation steps of silicon dioxide are prepared by chemical vapor deposition. The precursor and reaction chamber are prepared, and then the precursor and reaction gas are introduced, and the reaction is waited for completion. During the chemical vapor deposition process, the silicon-containing gas decomposes at high temperature to produce silicon dioxide. By optimizing the conditions of the chemical vapor deposition process, extremely high-purity silicon dioxide can be prepared.

[0069] By blending, copolymerizing or grafting silicone with silica, silicone-modified silica can be formed, which can reduce the internal stress of silica and form intramolecular toughening, thereby improving its high temperature resistance and brittleness resistance.

[0070] Table 1 below is a table of properties of silicon dioxide prepared in different embodiments and comparative examples:

[0071] Group brittleness strength Example 1 Low brittleness high Example 2 Low brittleness high Example 3 Low brittleness high Example 4 Low brittleness high Comparative Example 1 High brittleness Low

[0072] The test steps for silicon dioxide brittleness test are as follows:

[0073] A1. Sample preparation: preparing a silica sample;

[0074] A2. Prepare testing equipment and choose universal material testing machine or impact testing machine as testing equipment;

[0075] A3. Set the test parameters of the equipment, including loading speed, loading method and test temperature;

[0076] A4. Install the sample in the fixture of the test equipment to ensure that the sample is firmly fixed and evenly stressed;

[0077] A5. Start the test equipment, test the samples according to the set parameters, and observe and record the deformation and crack extension of the samples during loading;

[0078] A6. When the sample breaks, stop the test and record the relevant data, including the maximum load and breaking strength.

[0079] A7. Analyze the data and calculate the brittleness index of the sample;

[0080] The calculation formula is:

[0081] Where Ki is the output value, P is the maximum force that the sample can withstand, S is the distance between the sample and the support point, B is the sample thickness, and W is the width of the sample.

[0082] The test steps for silica hardness test are:

[0083] A1. Prepare the silica sample and ensure that the surface of the silica sample is clean, flat, and free of impurities or scratches;

[0084] A2. Install the sample, place it on the test bench of the Vickers hardness tester, and secure it to ensure that it will not move during the test;

[0085] A3. Apply pressure. Use the diamond triangular pyramid indenter on the Vickers hardness tester to press the indenter into the surface of the sample under a predetermined load. The load size and indenter shape should be selected according to the test standard or the characteristics of the material to be tested.

[0086] A4. Unloading pressure: After reaching the predetermined load, unload the pressure and remove the indenter. At this time, an indentation will be left on the surface of the sample.

[0087] A5. Observe the indentation. Use a microscope or other measuring tools to observe and record the size and shape of the indentation.

[0088] A6. Calculate the hardness value. According to the principle and formula of the Vickers hardness tester, the Vickers hardness value of silicon dioxide is calculated using the measured diagonal length of the indentation and the applied load.

[0089] The calculation formula is:

[0090] HV=1.8544F / D 2

[0091] Where F is the load value when the drill bit applies force, D is the square diagonal length of the drill bit's indentation, and HV is the Vickers hardness.

[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a modified silicon dioxide material for a lead-acid battery, characterized in that: The preparation steps are: S1. Prepare the following materials: 100-900 parts of quartz sand, 10-800 parts of carbonate, 1-520 parts of organosilicon, 1-300 parts of coupling agent, 1-210 parts of plasticizer and 100-800 parts of smelting waste slag; S2, treating the smelting waste slag, filtering out impurities, extracting components for preparing silicon dioxide, and setting them aside; S3, grinding and washing the quartz sand, mixing the reserved components in step S2 with the coupling agent and the plasticizer, putting them into carbonate, and reacting the quartz sand and the carbonate of the mixed material at high temperature to produce preliminary silicon dioxide; S4, filtering and washing the preliminary silica to obtain a silica product; S5, blending and copolymerizing the obtained silicon dioxide product with organosilicon to form a modified silicon dioxide material; S6. Conduct quality inspection on the modified silica material.

2. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: The specific amounts of materials in step S1 are: 800 parts of quartz sand, 600 parts of carbonate, 220 parts of silicone, 200 parts of coupling agent, 110 parts of plasticizer and 650 parts of smelting waste slag.

3. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: The quartz sand is one of river sand, sea sand, mountain sand and crystalline quartz sand, the carbonate is one of normal salt, acid salt and basic carbonate, the silicone is one of silicone monomer and silicone intermediate, the coupling agent is one of silane coupling agent, titanate coupling agent, aluminate coupling agent, bimetallic coupling agent, phosphate coupling agent and borate coupling agent, the plasticizer is one of aliphatic dibasic acid esters, phthalates and benzoates, and the smelting waste slag includes residues in ironmaking waste slag, steelmaking waste slag, ferroalloy smelting waste slag and light metal smelting waste slag.

4. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: The step of filtering out impurities from the smelting waste slag in step S2 is performed by placing the smelting waste slag into a crusher in advance for crushing treatment to reduce the particle size, utilizing the density difference of different metals to perform preliminary screening of metals and non-metallic substances in the waste slag through gravity screening equipment, and then utilizing the conductivity difference of different metals to perform secondary screening through electric separation equipment to screen out conductive metals and non-conductive metals, and finally dissolving the metal ions in the waste slag through acid leaching, and extracting the prepared silica component through precipitation crystallization.

5. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: In step S3, the quartz sand grinding step is performed by using a hammer crusher to crush the large particles of quartz sand into small particles, and then the small particles of quartz sand are ground by a dry method; the quartz sand washing step is performed by soaking the ground small particles of quartz sand in clean water for 5 hours. After the soaking time is completed, the small particles of quartz sand are taken out, sieved and filtered, and placed in the sun for drying, and the quartz sand is washed after the water is dried.

6. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: In step S3, the coupling agent and the plasticizer are mixed at the same time and added to the carbonate; the high temperature reaction temperature is 900° C. and the reaction time is 5 hours.

7. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: In step S4, a glass fiber filter is used for silica filtration. The transparent supernatant is first passed through the filter, and the suspended matter is precipitated. After the supernatant is poured out, the precipitate is filtered out with a filter, and a suction filtration operation is performed. Finally, a drying operation is performed to obtain filtered silica. The silica is washed by placing the filtered silica into clean water for cleaning to remove residual chemical solvents and impurities.

8. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: In step S5, the silica product is co-polymerized with the organosilicon through chemical bonding to form a modified composite material. An initiator is added to the mixed silica to initiate the polymerization reaction, and the reaction conditions are controlled to form a new polymer network structure during the polymerization process.

9. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 1, characterized in that: The quality test of the modified silicon dioxide material in step S6 includes testing the brittleness and strength of the silicon dioxide.

10. The method for preparing the modified silicon dioxide material for lead-acid batteries according to claim 9, characterized in that: The steps for testing the brittleness of silica are: A1. Sample preparation: preparing a silica sample; A2. Prepare testing equipment and select universal material testing machine and impact testing machine as testing equipment; A3. Set the test parameters of the equipment, including loading speed, loading method and test temperature; A4. Install the sample in the fixture of the test equipment to ensure that the sample is firmly fixed and evenly stressed; A5. Start the test equipment, test the samples according to the set parameters, and observe and record the deformation and crack extension of the samples during loading; A6. When the sample breaks, stop the test and record the relevant data, including the maximum load and breaking strength; A7. Analyze the data and calculate the brittleness index of the sample; The calculation formula is: Where Ki is the output value, P is the maximum force that the sample can withstand, S is the distance between the sample and the support point, B is the sample thickness, and W is the width of the sample.